Time Domain SAR Raw Data Simulation of Distributed Targets. (27th September 2010) - Dogan, Ozan; Kartal, Mesut
Abstract : In this paper, a time domain stripmap mode Synthetic Aperture Radar (SAR) raw data simulation including both the terrain and the targets is proposed. The simulator generates SAR raw data of a scene, involving both single and double reflections in a computationally efficient manner. The inputs of the simulator are the digital elevation model of the terrain, the 3D target model, and the parameters of the SAR system. The simulator extracts a geometrically accurate reflectivity map and generates the SAR raw data in time domain. The disadvantage of time domain method is justified to be tolerable by presenting experiments on modularity performance of the simulator. Also a novel method to decrease the time domain computational complexity of the SAR raw data generation is proposed. Our method has showed very promising results in representing the scattering characteristics, the raw data, and the time domain simulation flexibility.